(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Each period of informatization of education has two parallel branches of development – technological basis and innovative processes in the educational system itself. Significant expansion of functional computer capabilities leads to the development and emergence of new technologies for the preparation and presentation information on a computer screen using various technical means of preparation and presentation training material (audio, video), which are subsequently embedded in the computer itself. There is a new multi-media information preparation technology - multimedia